Prolonged Face Mask Use During COVID-19 Pandemic Contributes to Increased Symptoms and Signs of Dry Eye: A Systematic Literature Review - Anak Agung Fridami Dewi; I Gede Bayu Utama Putra (Sriwijaya Journal of Ophthalmology, 2023)
Introduction: Face mask has been a vital protective equipment against COVID-19 in this pandemic era. Several ophthalmic complaints have been associated with face mask use, leading to the term "mask-associated dry eye". There's still a question that arises whether the duration of use contributes to the condition. This review aimed to assess the correlation between prolonged face mask use on dry eyes. Methods: A thorough systematic search was performed through PubMed, Science Direct, and Google Scholar, following the PRISMA 2020 Guideline. Keywords were "mask associated dry eye," OR "dry eye AND face mask" OR "OSDI" OR "tear break up time" AND "COVID-19 pandemic". Results: A total of 1130 articles were identified, and only six cross-sectional studies met the eligibility criteria. Prolonged face mask use is correlated with decreased TBUT in four studies, decreased Schirmer score in two studies, and lower TM parameter in one study. Increased duration of wearing mask is correlated with more frequent symptoms and severity of dry eye according to either OSDI, SPEED Questionnaire or another unspecified questionnaire found in five studies. Conclusion: Prolonged face mask use during the COVID-19 pandemic contributes to increased symptoms and signs of dry eye.